2013
DOI: 10.1371/journal.pone.0078014
|View full text |Cite
|
Sign up to set email alerts
|

Spleen-Dependent Regulation of Antigenic Variation in Malaria Parasites: Plasmodium knowlesi SICAvar Expression Profiles in Splenic and Asplenic Hosts

Abstract: BackgroundAntigenic variation by malaria parasites was first described in Plasmodium knowlesi, which infects humans and macaque monkeys, and subsequently in P. falciparum, the most virulent human parasite. The schizont-infected cell agglutination (SICA) variant proteins encoded by the SICAvar multigene family in P. knowlesi, and Erythrocyte Membrane Protein-1 (EMP-1) antigens encoded by the var multigene family in P. falciparum, are expressed at the surface of infected erythrocytes, are associated with virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 84 publications
4
37
0
Order By: Relevance
“…This is true with regard to understanding the intra-eythrocytic development cycle (IDC) of the parasites growing and multiplying within RBCs over the course of their 24–72 h (depending on the species), but also in terms of pathogenesis and immune evasion strategies that are the result of antigenic variation mechanisms [20]. We have shown that the presence of SICAvar transcripts alone is not necessarily an indicator of the subsequent expression of the encoded SICA proteins in P. knowlesi and that the spleen plays a role in transcriptional or post-transcriptional regulatory processes [21]. Whether similar tactics govern certain gene and protein expression mechanisms in P. vivax remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is true with regard to understanding the intra-eythrocytic development cycle (IDC) of the parasites growing and multiplying within RBCs over the course of their 24–72 h (depending on the species), but also in terms of pathogenesis and immune evasion strategies that are the result of antigenic variation mechanisms [20]. We have shown that the presence of SICAvar transcripts alone is not necessarily an indicator of the subsequent expression of the encoded SICA proteins in P. knowlesi and that the spleen plays a role in transcriptional or post-transcriptional regulatory processes [21]. Whether similar tactics govern certain gene and protein expression mechanisms in P. vivax remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These biological differences include the expression in P. vivax (and P. cynomolgi [16]) of members of a multigene family called vir, which encodes several hundred small presumptive variant antigen proteins with multiple predicted localizations [1719]. This is in contrast to the ~60 member var gene family in P. falciparum and the related ~108 member SICAvar family in Plasmodium knowlesi , with each confirmed to encode large variant antigens that become positioned at the surface of the infected RBCs and undergo switching events in the course of an immune response [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Because the parasite is threatened by the immune system, it has evolved escape strategies, including the intriguing use of antigenic variation mechanisms [89; 90; 91]. Most notably, P. falciparum and P. knowlesi have large multigene families, respectively, called the var and SICAvar gene families with about 60 ( var ) and 100 ( SICAvar ) members, that encode related variant proteins with different antigenic phenotypes [92; 93; 94; 95]. This topic is discussed again further below in relation to modeling within and between host-infection dynamics.…”
Section: Malaria As the Paradigm Infectious Diseasementioning
confidence: 99%
“…Effective antigenic variation over long periods of time requires highly regulated and mutually exclusive gene expression, and this has indeed been well characterized in the case of the var genes [12]. Other families, including sicavar [13] and pir [14], appear to have similar dynamics, albeit with less tight mutually-exclusive regulation. In the case of P. falciparum, var genes are regulated by epigenetic silencing and expression switching [12], and additional antigenic diversity is generated within the~60-member gene family via frequent recombination during both mitosis and meiosis [15,16].…”
Section: Introductionmentioning
confidence: 95%